New Firm Creation - Klapper, Leora; Love, Inessa (World Bank, Washington, DC, 2012)
New data from the World Bank Group entrepreneurship snapshots show that new businesses are created at a faster rate in countries with good governance, a strong legal and regulatory environment, low corporate taxes, and less red tape. The data also show that nearly all countries experienced a sharp drop in business entry during the financial crisis. The decline in new firm creation was faster and more severe in countries hit harder by the crisis.